Effect of machine hammer peening conditions on β grain refinement of additively manufactured Ti-6Al-4V - Neto, Leonor; Williams, Stewart W.; Davis, Alec E.; Kennedy, Jacob R. (MDPI, 2023)
Ti-6Al-4V components built with wire plus arc additive manufacturing (WAAM) generally have long columnar β grains that cause anisotropic behavior when the material undergoes static and cyclic failure. Recently, machine hammer peening (MHP) has been proved to induce prior-β grain refinement in WAAM resulting in isotropic properties and increased strength. In this study, MHP was investigated for WAAM walls to establish the dependency of the β grain refinement on peening parameters, such as energy, tool radius, and distance between impact steps. All combinations of parameters investigated resulted in grain-refined microstructures. The plastic strain theory failed to explain these results, as the microstructure refinement achieved did not match the strain distribution obtained. Thus, a new theory of accumulated energy was proposed in which the dynamic deformation of the MHP process should also be taken into consideration. The mechanical properties for the MHP conditions showed higher strength and decreased anisotropy as the energy per length increased. This was attributed to the reduction in texture in the WAAM walls. Thus, when applying MHP, the energy per unit length is controlling the grain size obtained and improved mechanical properties can be achieved.
Keywords: machine hammer peening; wire plus arc additive manufacturing; titanium alloys; microstructure; grain refinement; mechanical properties